(untitled) (Communications in Computational Physics, 2020)
Particle dynamics in a turbulent channel flow is considered. The effects of particle concentration and Reynolds number on the particle velocity statistics are investigated. Four different particle response times, τ+=1, 5, 30 and 100, are examined for three different Reynolds numbers, Re∗=200, 360 and 790 (based on channel height and friction velocity). The particle concentration evolves with time and statistics obtained during three different sampling periods might be distinctly different. The mean and fluctuating particle velocities are substantially affected both by the particle response time and by the Reynolds number of the flow.